Molecular genotyping of human papillomavirus L1 gene in low-risk and high-risk populations in Bangkok - Pornsawan Leaungwutiwong (2018)
Copyright © 2015 American Sexually Transmitted Diseases Association All rights reserved. Background: Human papillomavirus (HPV) infections in Thailand are a public health concern, but information on HPV infection in sex workers and men who have sex with men (MSM) is limited. The aim of this study was to measure the prevalence and genotype distribution of HPV among low- and high-risk, HIV-negative populations. Methods: A total of 300 participants were categorized as general women, female sex workers, MSM, and MSM sex workers. Human papillomavirus infections were identified by the Papanicolaou test and nested polymerase chain reaction. A phylogenetic analysis of partial HPV L1 genes was performed. Results: Abnormal cytology was found in 5% of general women, 10% of female sex workers, 24% of MSM, and 28% of MSM sex workers. Human papillomavirus was detected in 9% of general women, 13% of female sex workers, and 30% in both MSM and the MSM sex workers. The prevalence of HPV high-risk genotypes was significantly higher in female sex workers and MSM, whereas low-risk genotypes and genital warts were significantly higher in MSM sex workers. Significantly more patients with genital warts and cervical intraepithelial neoplasia I/anal intraepithelial neoplasia I harbored low-risk genotypes, whereas those with cervical intraepithelial neoplasia II/anal intraepithelial neoplasia II harbored high-risk genotypes. Conclusions: High- and low-risk HPV genotypes persist in high-risk groups in Bangkok. Some genotypes infecting at-risk populations are not vaccine preventable. These findings may help to elucidate the prevalence of HPV infections in Thailand and serve as the basis for additional investigations into risk factors for these populations.